Analisis dan Perancangan Sistem Informasi Penjualan Underware Berbasis Web (E-Commerce) Pada PT. Target Makmur Sentosa - herman; Arijanto, Rudy (ALGOR, 2024)
With the rapid advancement of technology and the internet in all countries, this world has experienced tremendous progress. The invention of the computer as a device for processing data and the internet as the main tool in competition has changed the world to be more advanced. In addition, over time, the role of information technology has a positive impact in improving the quality of human life. Current sales information system at PT. Target Makmur Sentosa only offers to customers through sales and opening shops in shopping centers such as markets without having their own E-commerce website. In developing sales and increasing customers, an online website-based sales system was created to make it easy for consumers to get the products they want easily and efficiently by using the E-Commerce platform. The method used in this study uses data collection methods, namely by observing, interviewing, and studying the literature. Meanwhile, system development uses a Agile methodology or approach. Based on the research conducted, it produces a website-based sales information system using PHP and MySQL. And from testing the system with blackbox testing conducted by 2 testers, the system created was able to help the underware sales process become more efficient.